مواصفات الاختبارات اللغوية عبر TOAFL المؤسس على المهارات اللغوية - Riyadi, Agus; Labib, Refa Mughni (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
This research aims to find out the specifications of linguistics tests via TOAFL based on linguistics skills, which were implemented by the Departement of Arabic Language and Literature at College of Riyadlul ‘Ulum Tasikmalaya. It is considered one of the Islamic educational universities that is interested in the Arabic Language. The Departement of Arabic Language and Literature at this college has an important role in spreading and developing the Arabic Language. Students in this departement learned Arabic language subjects and skills through a variety of linguistic tests, orally and in writing. Before the end of their university programs, they had to participate in these tests, and they did not know their specifications. It is clear that this research is descriptive qualitative research using a case study. The researchers used documentation, interviews, and observation approaches to collect information. This research is also based on the descriptive and analytical study of Miles and Huberman. This result of this research revealed the specifications of the linguistic test in this section of listening, which include a test for understanding words and audible texts. Speaking skill includes a test of dialouge and conversation. Reading skill includes a test of filling in the blanks, vocabulary, and grammar. As for writing skill, it include a test of correcting and analyzing the paragraph, where these are: test are a scientific reference and a reference for all students, readers, and those interested in those honorable language. يهدف هذا البحث الوقوف على معرفة موصفات الاختبارات اللغوية عبر TOAFL المؤسس على المهارات اللغوية التي نفذها قسم اللغة العربية وآدابها بجامعة رياض العلوم تاسيكملايا. وهي تعتبر من إحدى الجامعات التربويّة الإسلاميّة التي تهتمّ باللّغة العربية، فقسم اللغة العربية وآدابها في هذه الجامعة له دور هام في نشر وتطوير لغة الضاد. وكان الطلاب بهذا القسم يتعلمون مواد اللغة العربية ومهاراتها بنوعية من ال ا ختبارات اللغوية المتنوعة شفويا وتحريريا. وقبل أواخر البرامج الجامعية وجب عليهم الاشتراك بهذه الاختبارات وهم لم يعرفو بموصفاتها. ويتضح أن هذا البحث من نوع البحث الكيفي الوصفي باستخدام الدراسة الحالة. واستخدم الباحث منهج الوثائق والمقابلة والملاحظة لجمع المعلومات. ويتم هذا البحث أيضا على الدراسة الوصفية التحليلية لميس وهوبرمان. وقد حصلت  نتيجة هذا البحث على كشف موصفات الإختبارات اللغوية بهذا القسم من الاستماع  التي تشمل على اختبار فهم الكلمة والنصوص المسموعة أما مهارة الكلام تشمل على اختبار المحاورة والتحويل والقراءة  تشمل على اختبار ملء الفراغ والمفردات والقواعد أما مهارة الكتابة تشمل على اختبار تصحيح وتحليل الفقرة حيث تكون هذه الاختبارات سهما علميا ومرجعا لجميع الطلبة وللقارئين ومهتمين بهذه اللغة الشريفة.